Trends of hepatitis B among hospital admissions at tertiary care hospital, Solapur - Rokade, Hemlata G.; Kotnis, Subhalaxmi D.; Mangulikar, Suresh K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Hepatitis B is a national and global public health problem. Various studies have supported the change in prevalence and trends of Hepatitis B. The aim of the study was 1) to study the trends of Hepatitis B according to age, sex and area of residence, 2) to study seasonality of Hepatitis B cases, 3) to find geographical predilection of Hepatitis B cases in Solapur city. Methods: The records of patients with Hepatitis B from January2012 to December2016 admitted to tertiary care hospital, was retrieved and studied. Statistical analysis used: Percentages, z test of proportions, ACF and PACF. Results: Out of 406 Hepatitis B cases, 51.97% belonged to 15 to 45 years of age. There was an increasing trend of Hepatitis B from age of 15 years up to 45 years. The male female ratio was 2.63:1. Fifty-seven percent cases were from urban areas. The proportion of cases from urban area decreased from 9.01% in 2012 to 6.01% in the year 2016. Contrarily, it increased from 5.78% in 2012 to 10.98% in 2016 in rural area. Hepatitis B cases appear to come in sharp rises and falls in these five years with no specific trend. PACF results showed no seasonality. Ward number17 reported maximum cases. Conclusions: The primary prevention for Hepatitis B should be targeted at 15 to 45years of age group. There is no seasonal variation seen in Hepatitis B infection. Areas observed with hot pockets must be screened and kept under surveillance.